Cultivating Pedagogy for Transformative Learning: A Decade of Undergraduate Agroecology Education - Horner, Catherine E.; Morse, Cheryl; Carpenter, Nell; Nordstrom, Karen L.; Faulkner, Joshua W.; Mares, Teresa; Kinnebrew, Eva; Caswell, Martha; Izzo, Victor; Méndez, V. Ernesto; Lewins, Scott A.; McCune, Nils (Frontiers in Sustainable Food Systems, 2021)
Existing scholarship on agroecology and food systems education within U.S. colleges and universities has focused primarily on preparing students to be professionals working in agrifood systems. Developing students' skills and competencies, though vitally important, may not suffice for supporting transformative learning. Transformative learning shifts students' perceptions and awareness and informs future actions, constituting a potential avenue for leveraging education to support transformations toward more socially just and ecologically viable agrifood systems. It is unclear, however, what pedagogies and educational practices enable transformative learning. This paper explores the integration of multiple pedagogical innovations within an advanced agroecology course taught at the University of Vermont. Over a decade, the teaching team has made iterative adjustments to course content and pedagogies with the goal of catalyzing action toward transforming agrifood systems. In this paper, we evaluate our pedagogical approach, asking: (1) How well do course content and pedagogy align with our definition of transformative agroecology as transdisciplinary, participatory, action-oriented, and political? (2) How well does our approach enable transformative agroecological learning, and how is that identified? We present our course evaluation as a case study comprising qualitative analyses of course syllabi, student comments on University-administered course evaluations, and most significant change (MSC) reflections. MSC reflections proved to be a valuable method for identifying and assessing transformative learning. Through a curricular review, we found that substantial changes to course content and evaluative assignments between 2010 and 2020 align with a transformative approach to agroecology. This is validated in students' MSC reflections, which provide evidence of transformative learning. In sharing evaluative results, processes, and insights, we aim to contribute to a broader movement of scholar educators committed to iteratively and collaboratively developing transformative pedagogies within agroecology and sustainable food system education. We contend that reflexive practice among educators is necessary to leverage education for transforming agrifood systems.